A first finding of the framboidal pyrite in the nummulite shell from the simferopolskaya formation (Eocene) of mountain Crimea - V. N. Komarov; P. E. Sinkin; G. V. Agafonova; E. V. Kovalchuk (Известия высших учебных заведений: Геология и разведка, 2016)
The paper considers the data, concerning the studying of the pyritized shell Nummulites sp. from the nummulite limestones of simferopolskaya formation (Eocene), referred to the nummulite zones Nummulites nemkovi, N. distans и N. polygyratus. The pyrites of two generations are discovered. The first one is the earliest diagenetic framboidal pyrite, connected with the crystallization of the amorphous iron sulfides, and the second one is an idiomorphic pyrite, which forms the aggregates in a form of crystals. Aggregates of the crystalloid pyrite obviously formed on the base of the pyrite framboids and represent the latest products of their recrystallization and recut. The detailed description of the framboidal formations is given. Among them the two compositional types are distinguished. Framboids are represented by the spherical and oval obj ects by size from 1,25 to 15,7 microns. They are built up with pyrite crystals, being from 0,26 to 1,08 microns in size. The only one nummulite shell, containing the pyrite framboids, which has been discovered up to the present time, can justify the ultimately rareness of the suitable for the framboids formation local centers of the reduction conditions. The obtained new data can be helpful for the solving of the question about the dependence of the crystallographic modifications of the framboids on the environment and about the criteria of the definition of the biogenetic nature of the framboidal structures.